Protein engineering to increase the potential of a therapeutic antibody Fab for long-acting delivery to the eye. Issue 8 (17th November 2017) - Tesar, Devin; Luoma, Jacob; Wyatt, Emily A.; Shi, Catherine; Shatz, Whitney; Hass, Philip E.; Mathieu, Mary; Yi, Li; Corn, Jacob E.; Maass, Katie F.; Wang, Kathryn; Dion, Michelle Z.; et al.
ABSTRACT: To date, ocular antibody therapies for the treatment of retinal diseases rely on injection of the drug into the vitreous chamber of the eye. Given the burden for patients undergoing this procedure, less frequent dosing through the use of long-acting delivery (LAD) technologies is highly desirable. These technologies usually require a highly concentrated formulation and the antibody must be stable against extended exposure to physiological conditions. Here we have increased the potential of a therapeutic antibody antigen-binding fragment (Fab) for LAD by using protein engineering to enhance the chemical and physical stability of the molecule. Structure-guided amino acid substitutions in a negatively charged complementarity determining region (CDR-L1) of an anti-factor D (AFD) Fab resulted in increased chemical stability and solubility. A variant of AFD (AFD.v8), which combines light chain substitutions (VL-D28S:D30E:D31S) with a substitution (VH-D61E) to stabilize a heavy chain isomerization site, retained complement factor D binding and inhibition potency and has properties suitable for LAD. This variant was amenable to high protein concentration (>250 mg/mL), low ionic strength formulation suitable for intravitreal injection. AFD.v8 had acceptable pharmacokinetic (PK) properties upon intravitreal injection in rabbits, and improved stability under both formulation and physiological conditions. Simulations of expected human PK behavior indicated greater exposure with a 25-mg dose enabled by the increased solubility of AFD.v8.